The Role of Self Stigma towards Psychological Well-Being in Leprosy Patient - Sayang Ajeng Mardhiyah; Muthmainah Muthmainah (HM Publisher, 2021)
Introduction. This study aims to determine the role of self-stigma towardspsychological well-being to the people who have had leprosy in South Sumatera. Thestudy hypothesis that there is a role for self-stigma towards psychological well-beingviewed from psychological distress in people who have had leprosy in SouthSumatera. Methods. The participants of this study were people who have hadleprosy who finished their medical treatment. The research sample was 112 peoplewho have had leprosy. This study used the consecutive sampling technique.Psychological well-being and self-stigma were measured by the scale. The researchused simple regression analysis. Results. The result obtained by the value of R=0.442, R square= 0.178, F= 11.821, and P= 0,000 (p<0,05). It was proved that self-stigma has a significant role in 17.8% towards psychological well-being. Conclusion.There is no difference in psychological distress based on the role of self-stigma andpsychological well-being of people who have had leprosy in South Sumatera.